The fierceness of fronted /s/: Linguistic rhematization through visual transformation - Calder, Jeremy (Language in Society, 2019)
This article explores the roles that language and the body play in the iconization of cross-modal personae (see Agha 2003, 2004). Focusing on a community of radical drag queens in San Francisco, I analyze the interplay of visual presentation and acoustic dimensions of /s/ in the construction of the fierce queen persona, which embodies an extreme, larger-than-life, and anti-normative type of femininity. Taking data from transformations—conversations during which queens visually transform from male-presenting into their feminine drag personae—I explore the effect of fluid visual presentation on linguistic production, and argue that changes in both the linguistic and visual streams increasingly invoke qualia (see Gal 2013; Harkness 2015) projecting ‘harshness’ and ‘sharpness’ in the construction of fierce femininity. I argue that personae like the fierce queen become iconized through rhematization (see Gal 2013), a process in which qualic congruences are construed and constructed across multiple semiotic modalities. (Iconization, rhematization, qualia, sociophonetics, gender, personae, drag queens)*
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; drag queen; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; san francisco; sciences humaines; thématiques; états-unis

Góor-jigéen: la resignification négative d’une catégorie entre genre et sexualité (Sénégal) - Christophe Broqua (Socio, 2019)
Dans de nombreux pays africains, il a existé et il existe encore parfois des figures institutionnalisées de la diversité de genre. C’est le cas, au Sénégal, du góor-jigéen, littéralement « homme-femme » en langue wolof. Évoquée dans certains récits d’observateurs dès le xixe siècle, cette figure a rarement été décrite ou analysée avec précision dans la littérature savante. Pendant longtemps, le góor-jigéen était un homme biologique présentant des attributs féminins et occupant préférentiellement certaines fonctions sociales. Son statut et sa place étaient reconnus au sein de la société sénégalaise. Progressivement, l’expression est devenue synonyme d’homosexuel masculin et elle est aujourd’hui le plus souvent utilisée comme une injure. Elle a donc connu une « resignification négative », traduisant la transformation d’une catégorie de genre en une catégorie d’orientation sexuelle. Cet article retrace l’histoire de la figure du góor-jigéen et analyse les conditions qui ont rendu possible la transformation de sa signification et de sa position sociales.
Keywords: LGBTQIA2+; afrique; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sénégal; thématiques

Butch-femme dynamics in Exodus 2-6 and 14: A lesbian-focused character study - Focht, Caralie (Theology & Sexuality, 2019)
This article assesses Exodus’ Egypt as lesbian bar culture of the 1940s and 1950s, treating the main characters of Moses, Pharaoh, Yhwh as competing butches for the femme, Israel. The article utilizes a gender reversal, queer-ideological critical approach in order to read the biblical text of Exodus 2-6 and 14 in the way accessible to the lesbian community.
Keywords: approches et analyses; bible; discipline; genre; personnes lesbiennes; queer; ressource en ligne; science des religions; sciences humaines

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Introduction : Un appartement sur Uranus et Lettre d’un homme trans à l’ancien régime sexuel dans Un appartement sur Uranus: chroniques de la traversée - Preciado, Paul B.; Despentes, Virginie (Un appartement sur Uranus: chroniques de la traversée, 2019)
Je ne suis pas un homme je ne suis pas une femme je ne suis pas hétérosexuel je ne suis pas homosexuel je ne suis pas bisexuel. Je suis un dissident du système sexe-genre. Je suis la multiplicité du cosmos enfermée dans un régime politique et épistémologique binaire...Je n'apporte aucune nouvelle des marges. Je vous offre un morceau d'horizon.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

Les amitiés radicales - Toffoli, Camille (Liberté, 2019)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; hétérosexisme; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; systèmes d'oppressions; thématiques; travail social; trs1205; états-unis